Jasmonic acid improves cadmium tolerance in rice (Oryza sativa) by reducing the production of nitric oxide - Ji Bo Yang; Hao Yu Wang; Jing Huang; Chuan Jin Shan; Jing Yan; Chong Wei Zhong; Die Hu; Qiang Zhang; Ren Fang Shen; Xiao Fang Zhu; Da Li Zeng (Ecotoxicology and Environmental Safety)
The involvement of jasmonic acid (JA) in the rice’s response to cadmium (Cd) stress is well recognized, though the underlying mechanisms remain unclear. In this study, exposure to Cd stress rapidly elevated endogenous JA concentrations in rice roots, meanwhile, a mutant coleoptile photomorphogenesis 2 (cpm2) which produces less JA, was more sensitive to Cd stress than its wild type (WT). JA mitigated Cd toxicity by decreasing Cd absorption in root cell wall and shoot, which was achieved by up-regulating the expression of the Cd-chelation and efflux-related genes such as OsHMA3, OsABCG36 and OsCAL1; down-regulating the transcript level of the Cd uptake and translocation-related genes, including OsHMA2, OsCCX2, OsNRAMP1/5, and OsZIP5/7. Additionally, a reduction in hemicellulose content was observed in the root cell wall. Further analysis indicated that the mitigation effect of JA on Cd accumulation was dependent on the inhibition of nitric oxide (NO) synthesis, as the NO donor SNP could diminish this effect. In summary, JA effectively reduced Cd content in rice by modulating the cell wall’s capacity for Cd uptake, potentially through reducing the production of NO.